HUBUNGAN KEPERCAYAAN DIRI DENGAN KEAKTIFAN SISWA DALAM DISKUSI KELOMPOK PADA MATA PELAJARAN AKIDAH AKHLAK - Ari Basuki; Hernawati; Asa Tsaaniyatu Fadhila (STAI Miftahul Ulum Tanjungpinang, 2023)
This study aims to determine the correlation between self-confidence and student activity in group discussions on Akidah Akhlak subjects at Madrasah Aliyah Negeri Bintan. Data were collected by interviews, observation, documentation, and distributing questionnaires. The subjects in this study were students of Madrasah Aliyah Negeri Bintan, with total 196 people. Samples were taken 30% of the total population, they were 59 people. The data were analyzed using the percentage formula and the product moment correlation technique with the SPSS application. The results of this study indicate that students’ self-confidence and student activity in group discussions have strong and significant positive correlation according to the results 0.733 and sig. 0.000.